Impact of Geometrical Parameters on Indoor Environments with Single-Sided Ventilation: Experimental and Numerical Study - Hasna Abid; Ridha Djebali; Hamza Faraji; Mariem Lajnef; Zied Driss; Jamel Bessrour (Journal of Applied and Computational Mechanics)
This paper presents a comprehensive investigation into the impact of geometrical parameters on indoor environments. The study utilizes an experimental setup and a developed numerical model, with validation achieved through comparison with test data from a cabin prototype, focusing on air velocity and temperature profiles. The numerical model undergoes optimization, including turbulence and grid independence analyses, to ensure accurate simulations. Additionally, the study explores the heat source effect on indoor thermal comfort through a series of numerical simulations. Based on the combined numerical and experimental findings, the study establishes robust correlations to explain the variations resulting from these factors. It highlights the crucial roles of roof height and room length in determining aerodynamic characteristics within the room. The study's comparative analysis shows that the Predicted Mean Vote (PMV) remains below 0.45 for a heat flux of 150 W.m-2, indicating a neutral thermal sensation. In contrast, it rises to 2.55 for a heat flux of 800 W.m-2, indicating a warm thermal sensation. Overall, this research provides valuable insights into the complex dynamics of airflow within indoor environments.